Product support and the new product development process - Anagnostopoulos, Z. (Cranfield University, 2006)
Product support is a key aspect in the industrial marketing of not only high-technology products but also heavy goods and software applications, since it strongly influences customer satisfaction and can also be an important source of revenue. Typical elements of product support include installation, user training, equipment maintenance and, if necessary, repair - all of these are normally provided by manufacturers’ support organisations. Despite its importance to several industries, support has not been extensively researched. This study describes the involvement of the support organisation in the new product development process. Several authors have identified that product support is dependent on product design. Consequently, the same authors emphasise that support should be thoroughly evaluated during product design. This study identifies the elements of product support that may be evaluated and shows in detail how four companies in different industrial sectors evaluate support when developing new products. To further investigate the topic, two similar products per company were selected: one easy and one difficult to support. The study investigated the differences in the development between the two products in terms of product support input in the new product development process. The results show that all companies had product support participating in their new product development processes, however product support was more involved in the easy than in the difficult to support products. Compared to other research works and research publications, this research project took a step deeper inside the NPD teams in order to investigate the involvement of product support, the actions and targets set and the influence of product support. Consequently, the study provides a foundation from which there is real scope for further management research into what is becoming recognised as a vital element of industrial marketing.